A Bibliometric Analysis of Islamic Business Ethics in the Context of the Global Economy - Judijanto, Loso; Ilhamiwati, Mega; Supriandi, Supriandi (West Science Interdisciplinary Studies, 2024)
This study employs bibliometric analysis to explore the scholarly landscape of Islamic business ethics within the context of the global economy. Through systematic data collection from major academic databases and the use of VOSviewer for network visualization, this research identifies key thematic clusters, author collaboration patterns, evolving research trends over time, and highlights underexplored areas with potential for future investigation. The findings reveal a robust focus on Islamic business ethics' application in banking and economic growth, the integration of technology in finance, and the sector's response to global crises such as the COVID-19 pandemic. Less saturated topics identified include Islamic tourism and culture, Islamic social finance, and comparative studies between Islamic and conventional banking systems. The study also maps out author collaborations, emphasizing the community's role in advancing research. These insights provide a comprehensive overview of the field, revealing both its current state and promising directions for future scholarly work.